2020
DOI: 10.2131/jts.45.117
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles enhance germ cell apoptosis by inducing reactive oxygen species (ROS) formation in <i>Caenorhabditis elegans</i>

Abstract: Silica nanoparticles (SiO 2 NPs) are widely used in daily life and can enter organisms through several pathways, often causing unpredictable toxicity. Although SiO 2 NPs are known to cause damage to the respiratory system, little is known about their oral toxicity, and their potential harm to the reproductive system is unclear. In this study, we used a Caenorhabditis elegans model to clarify SiO 2 NPs oral toxicity in vivo and explore their effect on the reproductive system. We exposed C. elegans to 0.25, 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The viability of C. elegans and A. simplex was investigated by monitoring the viability of the nematodes before and after BAM-HRP coating and post-hydrogel sheath coating. The viability of nematodes was determined based on the movement response following mechanical or touch stimuli [ [39] , [40] , [41] ].…”
Section: Methodsmentioning
confidence: 99%
“…The viability of C. elegans and A. simplex was investigated by monitoring the viability of the nematodes before and after BAM-HRP coating and post-hydrogel sheath coating. The viability of nematodes was determined based on the movement response following mechanical or touch stimuli [ [39] , [40] , [41] ].…”
Section: Methodsmentioning
confidence: 99%
“…SiO 2 and TiO 2 nanoparticles can also induce cytotoxicity and thus may have a negative health impact. These studies have shown that SiO 2 and TiO 2 nanoparticles show toxicity in the human lung, intestinal cells and during in vivo experiments [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the knowledge regarding the carrier effects of microplastics is mainly focused on persistent organic pollutants, heavy metals, and pharmaceuticals. Study on the interactions between microplastics and engineered nanomaterials is still limited, though both of them are constantly released into the aquatic environment through similar pathways, including wastewater, facility agriculture, and landfill (Gautam and Tiwari, 2020;Zhang et al, 2020).…”
mentioning
confidence: 99%